Calcium signaling in tunicate development - Joel C. Glover; Joel C. Glover; Oleg Tolstenkov; Yana Mikhaleva (Frontiers in Ecology and Evolution)
A comparative overview is provided of Ca2+ signaling and its potential mechanistic roles during development in tunicates. As background, the review presents an introduction to tunicate taxonomy, and then a general overview of Ca2+ signaling and methods for recording and measuring Ca2+ signals. It then covers the dynamics and implicated mechanisms of Ca2+ signals during different phases of development from oocyte to larva. These include signals arising in the unfertilized oocyte, signals associated with fertilization and meiosis, intercellular signals occurring from early cleavage stages through gastrulation, intercellular signals during organogenesis, and signals associated with early behavior. Comparisons are made among different tunicate species and where relevant to other chordate species. In many tunicate species, Ca2+ currents across the oocyte membrane are present prior to fertilization, and in the appendicularian Oikopleura dioica regular Ca2+ transients have been recorded optically prior to fertilization. Ca2+ signals at this stage have been implicated in pre-fertilization oocyte maturation events. The fertilization transient is the most well-studied Ca2+ signal and is triggered by factors from the sperm, including pivotally a phospholipase C (PLC) isoform that catalyzes the generation of IP3, which elicits release of Ca2+ from the endoplasmic reticulum. Post-fertilization signals are similarly dependent on IP3 signaling and are regulated by cyclin-dependent kinase 1 (Cdk1), and thereby linked to the meiotic divisions required for zygote formation. Ca2+ signals associated with early cleavages through gastrulation arise in blastomeres of the muscle lineage and spread from these in a coordinated fashion to other blastomeres through gap junctions. Post-gastrulation Ca2+ signals begin to show tissue-specificity in their temporal pattern as organogenesis proceeds, likely associated with loss of general gap junction transmission. Once neurulation has occurred, Ca2+ signals arise first in the nervous system and are transmitted synaptically to muscle, while Ca2+ signals arising spontaneously in the epidermis follow a separate temporal pattern. Species differences in the spatiotemporal characteristics of pre- and postgastrulation Ca+2 signals are discussed.